Labour market consideration as course selection criteria in a Malaysian university - Subramaniam, T.; Idris, H.; Mohd Ariff, M.R. (2011)
This paper aims to identify factors that are considered by the first year undergraduate students from Faculty of Arts and Social Sciences (FASS), University of Malaya in course selection process in two different stages namely pre-entry and post-entry. Findings from this study reveals that in pre-entry selection criteria, ‘teacher’ and ‘family’ factors appears to be more important. ‘Labour market consideration’ only appears to be the third important factor in this stage. These three factors collectively explains approximately 54 percent of the variation in pre-entry selection criteria. In postentry selection criteria, ‘peers influence’ , ‘orientation week’ and ‘limited choices’ factors emerged as important dimensions. These three factors in turn collectively explains approximately 49 percent of the variation in post-entry selection criteria. ‘Labour market consideration’ emerges only as the second last important factor in post-entry selection criteria.